2019
DOI: 10.1016/j.parepi.2019.e00121
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii seropositivity associated to peri-urban living places in pregnant women in a rural area of Buenos Aires province, Argentina

Abstract: Infection with Toxoplasma gondii is very common in humans throughout the world, the intake of raw or undercooked meat with tissue cysts and fruits, vegetables and water contaminated with parasite oocysts being the main routes of infection. Here, we analyzed the seroprevalence of anti-T. gondii antibodies in pregnant females (age 13–44 years; n = 920) between April 2014 and December 2017 from Chascomús (Argentina), a city immersed in a rural area. Altogether 320 tested positive for immunoglobulin G antibodies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
1
9
0
1
Order By: Relevance
“…These findings are consistent with the study by Al-Qurashi et al (2001) who reported that the highest seroprevalences of anti-T. gondii IgG were found among people who lived in rural areas, and Al-Mohammad et al (2010) suggested that rural living may correlate with increased exposure to soil potentially contaminated with oocysts ( Al-Qurashi et al, 2001 , Al-Mohammad et al, 2010 ). Moreover, recent data by Rivera et al (2019) confirmed that significant differences were found in serological prevalence analyzes between urban and peri -urban areas in Chascomus, Argentina. The authors, suggested that higher seroprevalence in peri -urban areas may be associated with poor socioeconomic conditions and/or poor peri -urban environments, which is a risk factor to be considered when planning health care for pregnant women ( Rivera et al, 2019 ).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…These findings are consistent with the study by Al-Qurashi et al (2001) who reported that the highest seroprevalences of anti-T. gondii IgG were found among people who lived in rural areas, and Al-Mohammad et al (2010) suggested that rural living may correlate with increased exposure to soil potentially contaminated with oocysts ( Al-Qurashi et al, 2001 , Al-Mohammad et al, 2010 ). Moreover, recent data by Rivera et al (2019) confirmed that significant differences were found in serological prevalence analyzes between urban and peri -urban areas in Chascomus, Argentina. The authors, suggested that higher seroprevalence in peri -urban areas may be associated with poor socioeconomic conditions and/or poor peri -urban environments, which is a risk factor to be considered when planning health care for pregnant women ( Rivera et al, 2019 ).…”
Section: Discussionmentioning
confidence: 73%
“…Moreover, recent data by Rivera et al (2019) confirmed that significant differences were found in serological prevalence analyzes between urban and peri -urban areas in Chascomus, Argentina. The authors, suggested that higher seroprevalence in peri -urban areas may be associated with poor socioeconomic conditions and/or poor peri -urban environments, which is a risk factor to be considered when planning health care for pregnant women ( Rivera et al, 2019 ).…”
Section: Discussionmentioning
confidence: 73%
“…Such results are in line with a previous study by Olariu et al which established the same trends in women (76 vs. 55.3%) ( 35 ) and in children (18.4 vs. 14.7%) ( 36 ). Other countries showed also higher seroprevalence rates in people from rural compared with urban areas: Mexico 32 vs. 12% ( 37 ) or Argentina 36.4 vs. 26.8% ( 38 ). This variation can be attributed to the lower socio-economic level in some rural areas compared with urban ones, as well as to the less easy access to some services, such as running water, in some of these areas.…”
Section: Discussionmentioning
confidence: 98%
“…The global prevalence of T. gondii is estimated to be between 30% and 65% [12]. Toxoplasmosis is an infectious and inflammatory syndrome linked with the poverty, rural areas as well as urban areas, while most cases are asymptomatic [13]. Both Centre of Disease Control and prevention (CDC) and National institute of Health (NIH) classified Toxoplasma to be among category B infections, which once infected the organisms reside in some tissues for the host's lifelong waiting for reactivation [14].…”
Section: Introductionmentioning
confidence: 99%